CHOICE OF STEEL AND PRODUCTION TECHNOLOGY AT PRODUCTION OF THIN-WALLED ELECTRICWELDED PIPES AND PRODUCTS OF THEM - O. R. Prudnikova; E. D. Shcherbakov; V. P. Lapin (Литьë и металлургия)
It is shown that using of the modern materials and production technologies enables to receive light-wall electric-welded pipes of different categories of drawing out (by analogy with categories of sheet iron drawing out).